Giant vesicles (GV) in colloidal system under the optical polarization microscope (OPM). (September 2017) - Khalid, Khalisanni; Noh, Muhammad Azri Mohd; Khan, M. Niyaz; Ishak, Ruzaina; Penney, Esther; Chowdhury, Zaira Zaman; Hamzah, Mohammad Hafiz; Othman, Maizatulnisa
Graphical abstract: Highlights: The unprecedented Optical Polarisation Microscope (OPM) observations of giant vesicles (GV) were reported in this article. By the use of OPM, these GV were foundas giant multilamellar vesicles (GMV) and giant unilamellar vesicles (GUV). The findings were also validated by rheological analysis. Abstract: This paper discusses the unprecedented microscopic findings of micellar growth in colloidal system (CS) of catalyzed piperidinolysis of ionized phenyl salicylate (PS − ). The giant vesicles (GV) was observed under the optical polarization microscope (OPM) at [NaX] = 0.1 M where X = 3-isopropC6 H4 O − . The conditions were rationalized from pseudo-first-order rate constant, kobs of PS − of micellar phase at 31.1 × 10 −3 s −1 reported in previous publication. The overall diameter of GV (57.6 μm) in CS (CTABr/NaX/H2 O)-catalyzed piperidinolysis (where X = 3-isopropC6 H4 O) of ionized phenyl salicylate were found as giant unilamellar vesicles (GUV) and giant multilamellar vesicles (GMV). The findings were also validated by means of rheological analysis.